Influences of the vehicle in the spreading and release of betamethasone. (9th February 2018) - Molesini, Sonia; Urto, Federica; Cvetkovska, Alexandra D; Bettoli, Vincenzo; Valacchi, Giuseppe; Pecorelli, Alessandra; Manfredini, Stefano; Vertuani, Silvia
Aim: We compared the performances of two different commercial products both based on betamethasone and an antibiotic but using different pharmaceutical vehicles: a polymer and lipid-enriched cream and a conventional oil-in-water emulsion.Methodology: Evaluation was conducted on a reconstructed human epidermis model. Moreover, skin barrier properties and cutaneous hydration of the two vehicles were evaluated on 20 human healthy volunteers.Results: Overall, the polymer and lipid-enriched formulation works as a film-forming product that retains the therapeutic agent for a long time, ensuring its penetration and absorption through the skin, and promoting skin hydration.Conclusion: The above characteristics are useful in the clinical setting, especially in the context of eczematous diseases with a strong xerotic component.